Challenges Regarding Digitalization in Construction - Simona STANCA (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2025)
In an era marked by rapid change and accelerated technological progress, the construction industry is already experiencing significant transformations due to the implementation of automation and digitalization. Digitalization in construction is an essential process for increasing efficiency, reducing costs, and improving sustainability. However, this transition faces multiple challenges. Among the main obstacles are the resistance to change by traditional firms, the lack of digital skills among employees, and the high costs of implementing advanced technologies. The difficult integration of digital solutions into existing processes, the lack of interoperability between platforms, and cybersecurity concerns are other major barriers. Overcoming these challenges can facilitate a sustainable digital transformation with significant benefits for productivity and building quality. Thus, digitalization becomes not only an opportunity, but also a necessity for the future of the construction industry. The paper analyses how digital technology is revolutionizing the construction sector, highlighting both the advantages and challenges generated by this technological change.